Ten new species of the Stegana (Steganina) shirozui species group (Diptera, Drosophilidae) from China - Chen, Xi-Peng; Chen, Hong-Wei (Zootaxa, 2012)
Ten new species of the Stegana (Steganina) shirozui species group are described from central to southwestern China: S. (S.)danbaensis sp. nov., S. (S.) dianensis sp. nov., S. (S.) glabra sp. nov., S. (S.) montana sp. nov., S. (S.) oligochaeta sp. nov., S.(S.) tentaculifera sp. nov., S. (S.) parvispina sp. nov., S. (S.) pianmaensis sp. nov., S. (S.) protuberans sp. nov., S. (S.) xishuangbanna sp. nov. A key to all the species of the shirozui group is provided.